2008
DOI: 10.1164/rccm.200707-1011oc
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary Effects of Chronic Obstructive Pulmonary Disease on Physical Activity

Abstract: Higher values of systemic inflammation and left cardiac dysfunction are associated with reduced physical activity in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
282
3
32

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(339 citation statements)
references
References 48 publications
20
282
3
32
Order By: Relevance
“…Details of the COPD population at the institute have been published previously [13]. Patients with COPD had to be free of an exacerbation for at least 2 months.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the COPD population at the institute have been published previously [13]. Patients with COPD had to be free of an exacerbation for at least 2 months.…”
Section: Study Populationmentioning
confidence: 99%
“…It incorporates a biaxial accelerometer that records steps per day, and physiological indicators of energy expenditure. In patients with COPD, the SenseWear Pro armband provides a valid and reproducible estimate of energy expenditure during walking at a slow to moderate pace in a laboratory setting [12], and a high correlation between steps per day and movement counts as measured by a different accelerometer [13].…”
mentioning
confidence: 99%
“…Measurement of B-type natriuretic peptide or N-terminal prohormone brain natriuretic peptide (NT-proBNP) is a good way to discriminate heart failure in COPD patients [98] and may be useful to distinguish acute COPD exacerbations from decompensated heart failure [99]. An elevated plasma NTproBNP is correlated with poor physical activity in COPD patients, suggesting that left defective left ventricular function may contribute to reduced performance [100]. There is some evidence that, if anything, the cardiac size is decreased at least in patients with emphysema and that the actual volume of intra-thoracic blood is also decreased in patients with hyperinflation.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…It was also found to be significantly increased in patients presenting with acute exacerbation of COPD. de Torres and co workers [29] indicated that serum CRP level significantly increased with the aggravation of disease and correlation was found with BODE index(r=0.17, p=0.050).A cross-sectional study performed by Henrik Watz et al [30] states that higher values of CRP are associated with reduced physical activity in patients with COPD. Sarioglu et al [31] investigated the relationship between the BODE index and disease duration, annual exacerbation and hospitalization rates, health related quality of life and systemic inflammatory markers like C-reactive protein and concluded that BODE index is a comprehensive, feasible and simple clinical scoring system in the evaluation of COPD.…”
Section: Discussionmentioning
confidence: 95%